The effect of Total productive maintenance on product quality: Analytical study of the opinions of a sample of employees of the General Company for Automobile Industry, Alexandria / Babel - Hatif Al-Fatlawi, Mithaq; Mahmoud Fahd, Yasser (Iraqi Journal for Administrative Sciences, 2024)
The research seeks to test the impact of comprehensive productive maintenance and the extent of its contribution to improving product quality. As the research presented a theoretical framework for the comprehensive production maintenance and product quality, then the relationship between them was analyzed through the opinions of a sample of employees of the General Company for the Automobile Industry / Alexandria. Where the researcher distributed (100) questionnaires to a number of employees of the company in question, and (99) questionnaires were retrieved, (95) of which were valid for statistical analysis with a response rate of (94%), as the data were analyzed using the statistical program (Smart PLS V. 20), (SPSS v.25), and the research reached a set of conclusions, including (the availability of comprehensive productive maintenance and the quality of products in the General Automobile Manufacturing Company / Alexandria research sample). Based on these conclusions, the researcher presented a set of recommendations, including (spreading the principles and concepts of comprehensive productive maintenance throughout the company through periodic bulletins and notice boards with the aim of establishing this philosophy among the individuals working in the company).